KINETIC AND THERMODYNAMIC ADSORPTION STUDIES OF METHYLENE BLUE ONTO ZEOLITE FROM AQUEOUS SOLUTION (FUDMA JOURNAL OF SCIENCES, 2021)
Zeolite was synthesized via hydrothermal method from sodium metasilicate and sodium aluminate solutions. The prepared sample was characterized by Fourier transform infrared (FTIR) spectroscopy, Scanning electron microscopy (SEM) and X-ray diffraction (XRD).The adsorption of methylene blue dye onto zeolite was studied. The adsorption experiments were carried out in batches and the effect of parameters such as concentration, pH, adsorbent dosage, temperature and contact time were investigated. The experimental data were fitted into the Langmuir and Freundlich Adsorption Isotherm. The result was fitted into pseudo- first order and pseudo- second order kinetic models. The thermodynamic parameters were also evaluated. The results revealed that maximum adsorption of methylene blue dye was achieved at a concentration of 20 mg/L and pH of 8.9. The adsorption process followed a Langmuir adsorption isotherm model with a correlation coefficient value of 0.9911. The negative value of standard enthalpy of adsorption, Î”Ho calculated as -9.4 kJmol-1 revealed the exothermic nature of the adsorption process, the negative value of standard entropy of adsorption, Î”So evaluated as -20.6 Jmol-1K-1showed that no significant change occurs in the internal structures of zeolite during the adsorption process and the negative value of Gibbs free energy, Î”Go obtained as -3.28 kJmol-1indicated the spontaneity of the adsorption process
Keywords: Zeolite, Adsorption, Kinetics, Thermodynamic parameter, Methylene blue